Artificial polymerizations in living organisms for biomedical applications - Chen, Yun (2024)
Within living organisms, numerous nanomachines are constantly involved in complex polymerization processes, generating a diverse array of biomacromolecules for maintaining biological activities. Transporting artificial polymerizations from lab settings into biological contexts has expanded opportunities for understanding and managing biological events, creating novel cellular compartments, and introducing new functionalities. This review summarizes the recent advancements in artificial polymerizations, including those responding to external stimuli, internal environmental factors, and those that polymerize spontaneously. More importantly, the cutting-edge biomedical application scenarios of artificial polymerization, notably in safeguarding cells, modulating biological events, improving diagnostic performance, and facilitating therapeutic efficacy are highlighted. Finally, this review outlines the key challenges and technological obstacles that remain for polymerizations in biological organisms, as well as offers insights into potential directions for advancing their practical applications and clinical trials.